Ritual Tumpek Wariga Sebagai Simbol Resiprositas: Studi Ekosofi - Hari, I Nyoman Hari Mukti Dananjaya; Yunitha Asri Diantary Ni Made (PATISAMBHIDA : Jurnal Pemikiran Buddha dan Filsafat Agama, 2025)
Land conversion in Bali is currently a muntidimensional issue that not only threatens food security and ecosystem balance, but also triggers environmental degradation. The situation demands a reconstruction of the relationship between humans and nature based on local wisdom values. The values of local wisdom can be the basis for building a deeper ecological awareness, such as the rituals performed by Indonesian people. The tumpek wariga ritual can provide a new perspective in the preparation of environmental conservation strategies, where with an ecosophical approach that emphasizes the importance of human involvement in maintaining the balance of the ecosystem. This research uses a descriptive qualitative method with a phenomenological approach. This research shows that tumpek wariga ritual as environmental preservation requires an approach that goes beyond technocratic policies, by integrating philosophical, cultural, and spiritual values of the community. The value of reciprocity in this ritual emphasizes the importance of the ethical relationship between humans and the environment rooted in local wisdom. Tumpek wariga is not only a sacred heritage, but also offers a future ecological narrative that is equitable and sustainable.